Estudio de impacto ambiental en el área de influencia del sistema de riego presurizado atapo-Palmira, microcuenca del Río Atapo - Benito Mendoza (2019)
The objective of this research was to measure the impacts generated at a social and environmental level by the operation of the Atapo - Palmira irrigation system project in the Atapo river microbasin. The methodology used in this study is divided into 2 parts: in the gathering information; and identification and assessment of impacts. In the first part, studies and information of the irrigation system were collected. A multitemporal analysis of the land cover was carried out in 2 time intervals 1999-2007 and 2007-2017 through geographic information systems. Laboratory analysis of soil in the micro-basin and irrigation areas was carried out; water quality analysis of the final springs and rivers; and surveys and interviews were applied to know the perception of the communities related to the project. In the second part, the identification and assessment of the impacts was carried out using the method proposed by Arboleda 1986, which evaluates the impact through 5 parameters: class, presence, duration, evolution and magnitude; Twenty-eight relevant, determinable and excluding environmental impacts were identified that were valued independently. The results of the investigation estimated that the project produces a positive and significant net environmental; and social impact due to the recovery of degraded soils; the increase of agriculture with agro-ecological practices; the decrease of the susceptibility of bare soils and dry vegetation to gain in relation to other more beneficial cover categories. The improvement gives the quality of forest plantations; by the increase of the economic income and the reduction of the work load; and the strengthening of community organizations. Finally, the contribution of this research is the development of a management plan with the mitigation and compensation measures for the negative impacts evaluated.